Implementation of Handling Actions for Health Problems Regarding Food Poisoning - Rejeki, Desi Sri; Djunaedi, Djunaedi (International Journal of Health Sciences, 2024)
Poisoning is an emergency that can damage cells and some body functions due to the entry of a substance or food that contains poison, originating from toxic materials formed due to the decomposition of food and bacteria. Food poisoning is an illness that occurs after eating food that contains toxins, originating from toxic materials formed as a result of food decay and bacteria. Research purposes is for know knowledge help first on poisoning food. Research Methods this is study descriptive with use approach cross sectional. Retrieval sample done with accidental sampling and collection data use questionnaire knowledge poisoning food with a analysis data using univariate analysis. Results which obtained majority respondent know definition poisoning, sign and symptom poisoning, and management poisoning. Majority respondent not yet know handling dehydration heavy and diarrhea which due to because poisoning.